2016
DOI: 10.1016/j.apergo.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The importance of work organization on workload and musculoskeletal health – Grocery store work as a model

Abstract: The importance of work organization on workload and musculoskeletal healthGrocery store work as a model. General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 45 publications
2
39
1
Order By: Relevance
“…There have been several reports of osteoarthritis of the temporomandibular joint due to forward head and mechanical pain in the head [4]. There are also some reports of radicular pain in the arms and hands due to osteoarthritis of the neck due to UCS [2]. Such adverse secondary changes resulting from this syndrome are also present in people with thoracic kyphosis in the glenohumeral joint [4,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports of osteoarthritis of the temporomandibular joint due to forward head and mechanical pain in the head [4]. There are also some reports of radicular pain in the arms and hands due to osteoarthritis of the neck due to UCS [2]. Such adverse secondary changes resulting from this syndrome are also present in people with thoracic kyphosis in the glenohumeral joint [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…uscle imbalance can affect the body's natural alignment and cause a variety of postural abnormalities [1]. Improper posture and long-term work tasks can lead to musculoskeletal disorders [2]. Early and timely identification of these postural defects and their treatment can reduce its complications and help save time and money [3].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study could be used when planning organizational actions to promote excellent work ability among young workers. Varied work might contribute to excellent work ability in men and plausibly a healthier workplace for all employees [ 31 , 32 ]. Also, facilitating worktime control could be one way to promote excellent work ability, especially for women with high work demands, though the awareness of other opportunities for recovery at work and in leisure may be more important.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, the retail sector employs about 500 000 individuals, with quite similar proportions of women and men 44. A previous Swedish study suggests that physical workloads may differ considerably between different tasks in a grocery store,45 and studies taking a sociological/etnographical perspective have confirmed a gendered distribution of tasks 38 46. Some tasks are considered ‘female’ and may therefore, because of gendered norms, be excluded from job rotations otherwise intended to lead to more attractive work for everybody.…”
Section: Introductionmentioning
confidence: 94%